The use of thromboelastography and the functional tests with double local hypoxia of the upper limb to assess the risk of thromboembolism in patients undergoing surgery - Tarabrin, O.; Gozhenko, A.; Vorotyntsev, S. I.; Kobelyatsky, Y.; Volkova, Y.; Nesterenko, O.; Snisar, V.; Sorokina, O.; Cherniy, V.; Dudukina, S.; Surkov, D.; Kirpichnikova, K.; et al. (My University, 2023)
Prothrombotic is considered a condition that leads to the development of venous or arterial thrombosis and its consequences. There are many factors that cause a violation of the hemostatic potential in patients undergoing surgery with existing risk factors for thromboembolism, a more detailed study of the blood coagulation system, including the study of the compensatory capabilities of the hemocoagulation system, should be conducted. One of these methods is a functional test with double local hypoxia of the upper limb (DLHUL) under the control of thromboelastography (TEG). Goals: The purpose of the study - to identify the degree of thrombotic risk in patients preparing for planned surgical intervention, who belong to the risk group of thrombotic complications, to compare and evaluate the state of the hemostasis system in healthy volunteers and in this cohort of patients using a functional test with double local hypoxia of the upper limb by the method of thromboelastography. Materials and methods: A randomized prospective study was conducted. Patients were divided into two groups depending on the presence of risk factors for thrombosis. Group 1 consisted of healthy volunteers (n = 40) who are not at risk of thrombosis. Group 2 includes patients with existing factors of thrombotic risk (n = 120) who are preparing for scheduled surgical interventions. These patients underwent a functional test of "double local hypoxia of the upper limb" (DLHUL) using thromboelastographic (TEG) methods of studying the hemocoagulation system. The main task of this functional test is to create a trigger component to determine the limits of hemostasis, the origin and duration of adaptive and compensatory reactions of the hemostasis system. Indicators of the hemostasis system are recorded using a thromboelastograph before and after the test. The links of hemostasis are reflected by the following indicators: aggregate state of blood (A0), contact coagulation intensity (CCI), coagulation drive intensity (ICD), maximum clot density - maximum activity (MA), fibrinolytic activity - clot retraction and lysis index (IRCL).
Keywords: hemostasis; thrombosis; deep vein thrombosis; pulmonary embolism; risk of thrombosis; perioperative management; thrombotic complications; thromboelastography